Right mainstem bronchoplasty 18 years following thoracic spinal implant surgery (2018)
Thoracic spinal surgery has many complications ranging from surgical site infection, chronic pain, periarticular arthrosis, displacement of spinal screws and hardware migration to a lesser degree. Reports of spinal implants penetrating the aorta have been described in the literature, however to our knowledge, lower airway obstruction due to spinal hardware migration has not been reported. Here we describe a case of a patient presenting with a right main stem bronchial obstruction and pneumonia secondary to the migration of the surgical spinal hardware into the lower airway 18 years after his initial intervention. We describe our surgical approach, management and outcomes using bronchoscopy and open thoracotomy. Bronchial obstruction is not a common complication of thoracic spinal surgery, however in remote cases patients may present with rare consequences, it is therefore important to pay close attention to patients' clinical and surgical history since surgical complications may appear years after.